Using Science, Technology, and Innovation (Sti); in Achieving Sustainable Development in Developing Countries (Dcs) - Maiwada, Umar Danjuma; Ahmad Aliyu Jamoh (Journal of Technology Innovations and Energy, 2022)
University-industry relations need to be strengthened; several institutions have technology transfer offices that assist in the formation of spin-off companies. On inventions and technologies, different commercialization routes, the functions of technology transfer offices, and diverse organizational structures will be examined. By showing current innovation and technology, this paper contributes to attaining sustainable development for developed nations by academic and agricultural industry report, development, and commercialization operations. This research aims to analyses and completely examine the scientific and technical literacy approaches for sustainable development in industrialized nations. The evident necessity of sustainable development on supporting scientific and technical advancement in the world's "developed," "developing," and "under-developed" countries is obvious. In this research, we look at how most countries maintain scientific and technical progress. The study also looked at the ideas that underpin the implementation of scientific and technical literacy, with a focus on sustainable development. As a result, proposals on how the Federal government or other agencies may promote sustainable interms of science, technology, including innovation were made.